Effect of Fertilizer Treatment and Harvesting Time on Principal Chemical Constituents of Oroxylum indicum Vent. and Andrographis paniculata Nees - Singson, M. Z.; Kumar, Rakesh; Bisht, R. S.; Rawat, Neelam (Indian Forester, 2010)
Analysis of two medicinal plants, Andrographis paniculata (Andrographolide) and Oroxylum indicum (mixture of oroxylin A & chrysin) content was carried out under different fertilizer treatments and at different physiological stages of plants. Total ash, water-soluble ash, acid insoluble ash, alcohol soluble extractives and water-soluble extractives for the above plant species were estimated alongwith thin layer chromatography examination. Maximum andrographolide content of 2.0% was found in 120 days old plants and among the treatments given to plants, the chemical fertilizer treatment influenced the Andrographolide, alcohol soluble extractive and water-soluble extractive. In case of Oroxylum indicum, all other evaluated compounds other than oroxylin-A and chrysin content were found to be almost similar whereas oroxylin-A and chrysin content was found maximum in mature tree root bark i.e. 0.7%. The results of present study show that fertilizer treatments given to plants and time of harvesting affect the chemical constituents of plants.